Design and synthesis of thiadiazole-oxadiazole-acetamide derivatives: Elastase inhibition, cytotoxicity, kinetic mechanism, and computational studies. (15th May 2023) - Hosseini Nasab, Narges; Raza, Hussain; Eom, Young Seok; Hassan, Mubashir; Kloczkowski, Andrzej; Kim, Song Ja
Graphical abstract: Highlights: A series of 1, 3, 4-thiadiazol-1, 3, 4-oxadiazol-acetamide derivatives (7a –7j ) were synthesized as elastase inhibitors. The in-vitro elastase inhibitory activity of all synthesized compounds was determined successfully. The kinetic mechanism was investigated by Lineweaver-Burk plots. MTT assay was used to evaluate the cytotoxicity of all compounds on B16F10 melanoma cell lines. Molecular docking was applied to investigate the binding affinity of compounds with elastase and the ligands showed good binding energy values. Abstract: Considering the biological significance of 1, 3, 4-thiadiazole/oxadiazole heterocyclic scaffolds, a novel series of 1, 3, 4-thiadiazole-1, 3, 4-oxadiazole-acetamide derivatives (7a –j ) was designed and synthesized using molecular hybridization. The inhibitory effects of the target compounds on elastase were evaluated, and all of these molecules were found to be potent inhibitors compared to the standard reference oleanolic acid. Compound 7f exhibited the excellent inhibitory activity (IC50  = 0.06 ± 0.02 μM), which is 214-fold more active than oleanolic acid (IC50  = 12.84 ± 0.45 μM). Kinetic analysis was also performed on the most potent compound (7f ) to determine the mode of binding with the target enzyme, and it was discovered that 7f inhibits the enzyme in a competitive manner. Furthermore, the MTT assay method was used to assess their toxicity on the viability of B16F10 melanoma cell lines, and all compounds did not display any toxic effect on the cells even at high concentrations. The molecular docking studies of all compounds also justified with their good docking score and among them, compound 7f had a good conformational state with hydrogen bond interactions within the receptor binding pocket, which is consistent with the experimental inhibition studies.